(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to examines the impact of neoliberalism on higher education, and the changes that have taken place in universities and colleges. The research method is theoretical and qualitative, and illustrates the progressive impact of neoliberal higher education ideas on higher education institutions and its spread, in order to serve the interests of economic and technological competition and market demands. Despite the increase in the number of institutions of higher education and the multiplicity of private colleges, which enable studies for a growing number of students, there are negative aspects to the approach of higher education; Changes in the cultural and administrative structure and orientation of academic institutions. This liberal trend directly affects the quality of education in addition to the commodification of education. The contributions of the private sector have multiplied in order to produce a professionally trained workforce, capable of integrating into the market and managing business and commerce - at the expense of the humanities, social sciences, arts and critical thinking. Moreover, there is a marked deterioration in the quality of education and its products in terms of academic efficiency and scientific research. The goal of education focuses on creating graduates without scientific or intellectual training, and on social interests.